An empirical study on customer perception towards online banking services evidences from selected provinces of Eastern Visayas. - Alas, Genesis Loreen A.; Angub, Andrea Faye J.; Nacional, Mary Grace A. (Tacloban City Genesis Loreen A. Alas, Andrea Faye J. Angub, and Mary Grace A. Nacional, 2019)
Online banking is the term used for today's new age of banking system. It uses the Internet as the delivery channel to conduct different banking transactions and offers various types of online services. The study was conducted online across selected provinces in the region of Eastern Visayas. The main objective of this study was to test bank customers on how they perceived online banking based on their likeliness to use. The study accumulated 124 respondents in the study composed both non-online and online banking users. Given from the socio-demographic profile of the respondents, majority are female, aged 18 to 25 years old and had at least college level of education. Different factors were determined why bank account users engage or not engage in online banking. The researchers also identified the satisfaction levels and types of problems encountered by online banking users. The collected data of the study were also analyzed through the use of ordinal logit regression. Significant factors that affect the likelihood to use online banking include sex, educational attainment, monthly income or allowance, type of bank account used, name of bank account, knowledgeability, how they learn about online banking, duration of use, and overall satisfaction. The researchers recommend that the bank should orient and provide knowledge to their customers of what online banking is, and the benefits of using this for the customers to utilize this service. The researchers also recommend to conduct the same study outside Eastern Visayas because results may vary depending on the region.
Undergraduate thesis (B.A.S.S. Economics) -- University of the Philippines, Tacloban.